Faster reproductive rates trade off against offspring growth in wild chimpanzees - Emery Thompson, Melissa (Proc Natl Acad Sci U S A, 2016)
Life history theory predicts a trade-off between offspring quality and quantity. Among large-bodied mammals, prolonged lactation and infant dependence suggest particularly strong potential for a quality–quantity trade-off to exist. Humans are one of the only such species to have been examined, providing mixed evidence under a peculiar set of circumstances, including extensive nutritional provisioning by nonmothers and extrasomatic wealth transmission. Here, we examine trade-offs between reproductive rate and one aspect of offspring quality (body size) in wild chimpanzees (Pan troglodytes schweinfurthii), a species with long periods of infant dependence and little direct provisioning. Juvenile lean body mass, estimated using urinary creatinine excretion, was positively associated with the interval to the next sibling’s birth. These effects persisted into adolescence and were not moderated by maternal identity. Maternal depletion could not explain poor offspring growth, as older mothers had larger offspring, and low maternal energy balance during lactation predicted larger, not smaller, juvenile size. Instead, our data suggest that offspring growth suffers when mothers wean early to invest in new reproductive efforts. These findings indicate that chimpanzee mothers with the resources to do so prioritize production of new offspring over prolonged investment in current offspring.